2021
DOI: 10.18280/ts.380401
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory and Motion Artefacts Removal from ICG Signal Using Denoising Techniques for Hemodynamic Parameters Monitoring

Abstract: The impedance cardiography (ICG) is a reliable, non-invasive method widely used in clinical practice for the measurement of a multitude of hemodynamic parameters for the diagnosis of cardiovascular disease and continuous monitoring. Signal processing field is necessary to eliminate noises as an artefact of respiration and movement, to extract features characteristics from ICG signals. This paper discusses the concept of wavelet denoising based on scale-dependent thresholding, which is used in two types of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The results revealed that the Db wavelet with order 8 (db8) exhibited superior performance, surpassing the other wavelet families. Nonetheless, there is ongoing interest by some research teams who have reported the promising performance of the Sym wavelet for denoising the conventional ICG signals (Thorax-ICG) [31,32], and other studies reported the suitability of both the Db and the Sym wavelet families for other biomedical signals, such as EEG, EMG and ECG [33][34][35][36]. However, the refined question of which of these wavelets would be more suitable for denoising the Arm-ICG waveform characteristics on a BbyB basis needs to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the Db wavelet with order 8 (db8) exhibited superior performance, surpassing the other wavelet families. Nonetheless, there is ongoing interest by some research teams who have reported the promising performance of the Sym wavelet for denoising the conventional ICG signals (Thorax-ICG) [31,32], and other studies reported the suitability of both the Db and the Sym wavelet families for other biomedical signals, such as EEG, EMG and ECG [33][34][35][36]. However, the refined question of which of these wavelets would be more suitable for denoising the Arm-ICG waveform characteristics on a BbyB basis needs to be addressed.…”
Section: Introductionmentioning
confidence: 99%